PEMANFAATAN MASJID JAMI’ SULTAN SYARIF ABDURRAHMAN SEBAGAI SUMBER BELAJAR SEJARAH - Ika Rahmatika Chalimi; Haris Firmansyah (Jurnal Pendidikan Sejarah Indonesia, 2020)
Abstract: This research aims to determine how teachers can use the Jami 'Sultan Syarif Abdurrahman Mosque as a source of learning history. The research method used qualitative research with the form of descriptive analysis. This research was do at SMAN 5, SMAN 6 and SMAN 9 Pontianak. Data collection techniques in this research used indepth interviews, observation and recording of documents and archives. The data analysis technique used data reduction, data presentation and conclusions withdrawal and verification. The research result shows (1) the advantage of the Jami 'Sultan Syarif Abdurrahman Mosque as a learning resource was carried out in various ways of planning, one of which was to first analyze learning resources that were in accordance with Basic Competencies (KD) and learning objectives, then design materials and modify them according to needs. ; then explaining it to the school in order to get a response and permission to be implemented. (2) The way history teachers at SMAN 5, SMAN 6 and SMAN 9 Pontianak City use the Jami 'Sultan Syarif Abdurrahman Mosque as a learning resource is inviting students to research the mosque, telling local stories about mosque as a historical heritage or Islamic history in Pontianak, asking students who have been go to the Jami 'Sultan Syarif Abdurrahman Mosque to tell how the mosque looks like and attach videos or pictures of the Jami' Sultan Syarif Abdurrahman Mosque. Learning evaluation was carried out in several ways including giving essays togroup assignments, combining it with the make a match learning model and making observations. (3) There are several obstacles and solutions made by history teachers so that the use of the Jami 'Sultan Syarif Abdurrahman mosque can be considered effective in achieving learning objectives.